Design and Development of a Wheelchair Prototype - Nguyen, Van-Tinh; Tung, Tran Thanh (Engineering, Technology & Applied Science Research, 2024)
The rate of people with disabilities in Vietnam is about 7% out of a total of 98 million. Wheelchairs are popular assistive devices for disabled people and are often found in many places around the world, including Vietnam. This study proposes a novel design of a prototype electric wheelchair to support people with disabilities in Vietnam. The electric wheelchair model was successfully simulated and manufactured, fully meeting the proposed technical requirements. The proposed model works well and is suitable for the shape and physical strength of Vietnamese people.